Effect of Ag cathode deposition rate on the performance of organic light-emitting diodes. (October 2020) - Xie, Jiaqi; Li, Peicheng; Ho, Kevin; Walker, Gilbert C.; Lu, Zheng-Hong
Abstract: The effect of deposition rate of silver (Ag) cathode on the device performance of organic light-emitting diodes (OLEDs) has been investigated. The leaky current before the turn-on of devices was observed in the samples that have the Ag cathode deposited at relatively low rate (less than 0.5 Å/s), and their emission efficiencies were found to be undesirably inconsistent. These issues were not observed in the samples that have Ag cathode deposited at higher rate (>1.0 Å/s). Here we show that the pixel-to-pixel uniformity of OLEDs employing Ag cathode can be simply improved by depositing the cathode at high rate, since the rapid deposition suppresses the Ag diffusion into underlying organic layer. Highlights: High thermal deposition rate of Ag cathode could effectively reduce current leakage and improve the emission uniformity for large-area OLEDs. The low-rate processed Ag cathode could blur the cathode/organic interface and the interfacial metal diffusion was problem trigger. High-rate processing was more capable to immobilize Ag clusters, and thus refining cathode morphology and structure.